A Single Case Study on the Ayurvedic Management of Cerebral Palsy - Biswal, Ambuja Kumar; Das, Arun Kumar; Rout , Diptimayee; Beher, Sriyanka Sonpari (International Research Journal of Ayurveda & Yoga, 2023)
Cerebral palsy (CP) is considering as a non-progressive neuromotor disorder of cerebral origin. It includes heterogeneous clinical states of variable etiology and severity ranging from minor incapacitation to total handicap. In India 1.77% of the population has some form of disability. Spastic cerebral palsy is most common and incidence is 60% to 70% of all cerebral palsy case. It cannot be correlated with any single disease or condition in Ayurveda, as it is a multi-factorial disease with clinical features of a wide variation. It can be taken as Vatavyadhi as far as its etiology and symptoms are concerned. Here, an effort was made to treat a 5-year-old male child with spastic diplegic. Cerebral Palsy using multiple Ayurvedic treatment modalities. 3 Month oral medicine and Pañcakarma procedures resulted in better improvement in sign and symptom of cerebral palsy.